Категорія соціальної відповідальності в світлі сучасних тенденцій формування відповідальної особистості - Чернета, Світлана Юріївна; Cherneta, Svitlana Yu. (Чернігівський національний педагогічноий університет, 2014)
Соціальна відповідальність особистості як актуальної проблеми сучасного українського суспільства розглядається через призму суспільної необхідності. В статті аналізуються наукові підходи до визначення поняття «відповідальність», яка реалізує свою соціальну функцію у соціальній відповідальності, що розкривається завдяки аналізу різних підходів.In the article actuality of problem of social responsibility of personality opens up in modern terms. It is marked on that to the state necessary citizens that can independently make decision and responsible for their choice. Problem of forming of social responsibility of personality of Ukrainian citizens, in the modern terms of overvalue of values, change of social ideals and necessity of self-feedback in behalf on the state becomes one of priority. Specified on that the analysis of scientific researches and modern socio-political situation of the state testifies that present contradictions between modern requirements to personality of specialists and level of formed their social responsibility as important condition that provides successful implementation of decision of problems and construction of democratic society. A conceptto "responsibility" is analysed through the prism of different sciences : philosophy, sociology, psychologies, ethicsand pedagogics. Considering the base of scientific and theoretical view sauthorial interpretation of concept of responsibility is given as personality quality that consists in realization of necessity of implementation of norms (inparticular, personality), and also ability of individual adequately to perceive the just estimation of the accomplished acts, estimate own operating under positions of humanity and clean conscience. Social responsibility is examined as a major element of intercommunication of person and society, and carries out the function of adjusting of behavior of individual in accordance with the requirements of society. With development of society responsibility purchased a leading role in political, spiritually-ideological and other relations; her improvement is the necessary condition of community development. Social responsibility of students is quality, that characterizes the social typical of personality, her inclination to restrain in the behavior the social norms universally recognized in this society, ability to choose certain behavior, independently to formulate moral duties, require from itself their implementation, to carry out estimate, self-control, be ready to be responsible for the actions.
A category of social responsibility is in the light of modern tendencies of forming of responsible personality
Keywords: responsibility; personality; socialquality; socialresponsibility; behavior; society; відповідальність; особистість; соціальна якість; соціальна відповідальність; поведінка; суспільство